식용 고구마 신품종 ‘다호미’ - 이형운(Hyeong-Un Lee); 정미남(Mi-Nam Chung); 이준설(Joon-Seol Lee); 송연상(Yeon-Sang Song); 한선경(Seon-Kyeong Han); 김재명(Jae-Myung Kim); 안승현(Seung-Hyun Ahn); 남상식(Sang-Sik Nam); 김학신(Hag-Sin Kim); 서세정(Sae-Jung Suh); 박광근(Kwang-Geun Park) (Korean journal of breeding, 2015)
‘다호미’는 국립식량과학원 바이오에너지작물연구소에서 2012년에 육성한 식용 고구마 품종으로 2005년에 ‘무안4호’를 모본으로, ‘진홍미’를 부본으로 하여 인공교배 하였다. 2007년부터 2008년까지 계통선발시험과 2009년부터 2010년까지 생산력검정시험을 실시하여 괴근 수량성, 상품성, 식미가 우수한 MI2005-05-04 계통을 ‘목포80호’로 계통명을 부여하였다. 2011년부터 2012년까지 2년간 지역적응시험을 수행한 결과, 괴근의 수량성, 상품성이 우수하고 식미가 양호하여 2012년 12월 농촌진흥청 농작물직무육성신품종선정심의회에서 신품종으로 선정되어 ‘다호미’라 명명하였다. ‘다호미’는 잎의 결각이 3개 내지 5개이고, 결각의 깊이는 보통이며 엽색, 잎자루색, 줄기색은 녹색이다. 괴근의 껍질색은 홍색, 육색은 담주황색이며 괴근 모양이 방추형으로 균일하여 상품성이 우수하다. ‘다호미’는 덩굴쪼김병에 강한 편이나 뿌리혹선충에는 저항성이 없다. ‘다호미’는 육질이 중간질이고 전분가는 20.9%으로 낮은 편이며 당도는 24.8 Brix°이고 총유리당은 생고구마가 9.7, 찐고구마가 32.0 g/100g (D.W.)으로 ‘율미’보다 높다. ‘다호미’는 조기재배시 상품괴근수량이 26.3 MT/ha으로 ‘율미’의 17.3 MT/ha보다 52% 증수되었다. 적기 및 만기재배시 상품괴근수량은 21.9 MT/ha으로 ‘율미’보다 35% 증수되었으며 주당상품괴근수는 2.8개/주, 상품괴근평균중은 138 g이다. ‘Dahomi’, a new sweetpotato variety, was developed for table use by the sweetpotato breeding team of Bioenergy Crop Research Institute, National Institute of Crop Science (NICS), RDA in 2012. This variety was derived from the cross between ‘Muan4’ and ‘Jinhongmi’ in 2005. The seedling and line selections were performed from 2007 to 2008, preliminary and advanced yield trials were carried out from 2009 to 2010, and the regional yield trials was conducted at five locations from 2011 to 2012 and it was named as ‘Dahomi’. This variety has three or five lobes leaf, green leaf, stem, and petiole. Storage root of ‘Dahomi’ was elliptic, red skin, light orange flesh. This variety is resistant to fusarium wilt, but susceptible to root-knot nematode. Texture of steamed storage root was intermediate, and degree Brix of steamed storage root was 24.8 °Brix. The total sugar content of raw and steamed storage root was 9.7, 32.0/100 dry weight (g), respectively, which was higher than that of ‘Yulmi. Storage root yield of ‘Dahomi’ was 26.3 MT/ha under the early seasonal cultivation, which was 52% higher than that of ‘Yulmi’. Storage root yield of ‘Dahomi’ was 21.9 MT/ha under the optimum and late seasonal cultivation, which was 35% higher than that of ‘Yulmi’. The number of storage roots over 50 g per plant was 2.8 and the average weight of storage root was 138 g under the optimum and late seasonal cultivation.